High tibial osteotomy: our experience with hemicallotasis method - Pogliacomi, F.; Defilippo, M.; Guardoli, A.; Scaravella, E. (Acta Biomedica Atenei Parmensis, 2014)
Despite the many progresses and ever better outcomes in knee arthroplasty, surgical osteotomy in this area of the body is still commonly used. Valgus high tibial osteotomy (HTO) through external fixator progressive distraction (hemicallotasis) has given good results in the treatment of varus knee deformities. Such surgical techinque, once all controindications and favorable factors have been identified, allows to progressively correct the deformity with extreme precision without using internal fixation devices or bone grafts. The positive outcomes in all 24 subjects included in our study affected with varus knees and initial medial osteoarthritis confirm the validity of this osteotomy technique.